2016
DOI: 10.1007/s40261-016-0464-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pregabalin for the Treatment of Neuropathic Pain in Patients Undergoing Hemodialysis

Abstract: UMIN000023117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Details of the 40 included studies 14-53 are reported in Table 2 and include data from 963 269 patients from 21 countries. Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,16-18,20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, 14-24,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the 40 included studies 14-53 are reported in Table 2 and include data from 963 269 patients from 21 countries. Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,16-18,20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, 14-24,…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 40 studies, 17 included a prevalence measure of overall analgesic use, 14,[16][17][18]20,23,25,29,33,36,37,43,45,46,48,49,52 33 included a prevalence measure of one or more specific analgesic drug class, defined as opioid, NSAID, adjuvant, and nonopioid, [14][15][16][17][18][19][20][21][22][23][24][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]50 and 18 measured the prevalence of one or more specific analgesic drug, including acetaminophen.…”
Section: Details Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Common side effects include dizziness, somnolence, dry mouth, and constipation. 136,137 Gabapentin is initiated as a single 600 mg dose on day 1 and increased every 3 days to a dose of 1800 mg, divided in 3 doses. The maximum analgesic dose of gabapentin recommended for adults is usually between 1,800 and 3,600 mg per day.…”
Section: Management Of Patients With Neuropathic Corneal Painmentioning
confidence: 99%
“…Pregabalin has been investigated for use in cancer-induced bone pain [74] and as a premedication to provide postoperative analgesia [75, 76]. Pregabalin can be an effective treatment for peripheral neuropathic pain provided adverse reactions are carefully monitored and dosages are correctly determined [77]. It demonstrates good bioavailability (≈98 %), minimal drug interactions, and low protein binding [78].…”
Section: Newer Antiepileptic Drugsmentioning
confidence: 99%